Investigating the Effects of Temperature on Photoplethysmography. Issue 20 (2015) - Khan, Musabbir; Pretty, Christopher G.; Amies, Alexander C.; Elliott, Rodney; Shaw, Geoffrey M.; Chase, J. Geoffrey
Abstract: Pulse oximetry is a commonly used technique to determine arterial oxygen saturation (SpO2 ) and heart rate. This method uses photoplethysmography (PPG) signals to estimate SpO2 . However, pulse oximeters can be less accurate at cold temperatures. In this research, the effects of temperature on PPG signal quality was investigated for a group of 20 adult volunteers. Raw PPG data was obtained using a custom pulse oximeter (PO) system. Three tests were performed with the subject's hand maintained at baseline, cold, and warm temperatures. Analysis showed the median PPG signal RMS, as an indicator of signal-to-noise, for the warm test was 0.0289 V [IQR = 0.0262 - 0.0315 V] compared to the baseline test's 0.0174 V [IQR = 0.0104 - 0.0285 V] and the cold test's 0.0066 V [IQR = 0.0053 - 0.0106V]. This improvement of up to 4x in signal quality was associated with a closer match between the SpO2 values estimated by the PO system and a commercial pulse oximeter. Paired RMS value comparison between the three tests showed a statistically significant difference for all P-values (P < 0.004). Results indicate that warm temperatures improve PPG quality and thus pulse oximeter accuracy.